Traffic light fault detection system - Che Soh, Azura; Mohd Noor, Samsul Bahari; Wagiran, Rahman; Sulaiman, Nasri; Mohd Sidek, Roslina (Universiti Putra Malaysia Press, 2002)
This paper presents the design and development of traffic light fault detection system as a first stage of further investigation in traffic light failure monitoring system[5]. In order to do that, a survey has been conducted to evaluate the behaviour of road users when approaching a junction. Based on that, different failures were grouped into three categories i.e. Highly Critical, Critical and Non Critical. A system to detect the condition of the lights based on the categories has been developed using photodarlington and combinational logic. The combinational logic circuit has been successfully simulated and implemented to classify the type of traffic light malfunction.